2020
DOI: 10.1002/eat.23337
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of intensive cognitive behavioral therapy in adolescents and adults with anorexia nervosa

Abstract: Objective This study aimed to compare the effectiveness of an intensive treatment based on enhanced cognitive behavioral therapy (CBT‐E) in adolescent and adult patients with anorexia nervosa. Methods A total of 150 consecutive patients (74 adolescents and 81 adults) were admitted to a 20‐week intensive CBT‐E program (13 weeks of inpatient followed by 7 weeks of day‐hospital treatment). All patients had responded poorly to previous outpatient treatments and were assessed at admission, end of treatment (EOT), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 47 publications
4
25
0
1
Order By: Relevance
“…The first is that, after treatment, the network becomes less densely connected, both in terms of global strength and the strength of the connections within the networks, a result that confirms the network theory (Borsboom, 2017) suggesting that a reduced density of connections after treatment indicates a treatment-induced psychopathology improvement (i.e., a reduced probability of symptom activation). Moreover, this finding is in line with our findings obtained using inferential statistical analysis that indicated significant improvements in BMI, eating-disorder behaviors and psychopathology after CBT-E, and confirms previous data on the effectiveness of intensive CBT-E (Dalle Grave et al, 2013;Dalle Grave et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The first is that, after treatment, the network becomes less densely connected, both in terms of global strength and the strength of the connections within the networks, a result that confirms the network theory (Borsboom, 2017) suggesting that a reduced density of connections after treatment indicates a treatment-induced psychopathology improvement (i.e., a reduced probability of symptom activation). Moreover, this finding is in line with our findings obtained using inferential statistical analysis that indicated significant improvements in BMI, eating-disorder behaviors and psychopathology after CBT-E, and confirms previous data on the effectiveness of intensive CBT-E (Dalle Grave et al, 2013;Dalle Grave et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have confirmed the effectiveness of both outpatient and intensive CBT-E for anorexia nervosa Calugi, Sartirana, Frostad, & Dalle Grave, 2021;Dalle Grave, Calugi, Conti, Doll, & Fairburn, 2013;Dalle Grave, Conti, & Calugi, 2020;Dalle Grave, Sartirana, & Calugi, 2019;Fairburn et al, 2013), but the specific mechanisms producing these improvements in eating-disorder psychopathology are still unknown. In fact, the assessment of eating-disorder features and psychopathology with traditional inferential statistical analysis has revealed no robust predictors of change or relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Hoste's ( 40 ) description of a FBT-informed DP in the USA heavily emphasizes the importance of the parents by placing them in charge of meals, encouraging parental persistence in the face of their child refusing food, not offering meal replacements and the less-directive role staff play to ensure they do not disempower parents. Alternatively, CBT-E based programmes prioritize involving the young people in decision making throughout the process, emphasizing the voluntary nature of the programme, with the view that this empowers the young person to take control over the process ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies investigating intensive outpatient treatments only (half-days and <5 days per week, or not positioned as alternatives to inpatient treatment) or adjunctive multi-family therapy groups are not included in this review. Programs that report outcomes for combined inpatient and DP treatment are also excluded [e.g., ( 18 21 )] as they do not typically function as alternatives to inpatient treatment. Rather they often act as step-down transition programmes between inpatient units and the community and typically aim to reduce admission lengths and readmission rates.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, weight restoration is a primary goal for AN treatment, but rapid and continued weight gain is often only achievable with intensive inpatient treatment, especially when body weight is extremely low (e.g., Resmark et al, 2019). Still, a substantial proportion of adolescents and adults receiving inpatient treatment for AN do not achieve remission at end of treatment (Dalle Grave et al, 2020;Isserlin et al, 2020;Schlegl et al, 2016;Schlegl et al, 2014). Thus, it is necessary to identify potential early predictors of treatment outcome to increase treatment success and prevent prolonged inpatient treatment.…”
mentioning
confidence: 99%